Discectomy for Primary and Recurrent Prolapse of Lumbar Intervertebral Discs - Kamrul Ahsan; Kamrul Najmus-Sakeb; Alamgir Hossain; Shahidul Islam Khan; MA Awwal (Journal of Orthopaedic Surgery, 2012)
Purpose. To reviewed 416 patients who underwent discectomy for primary or recurrent prolapse of lumbar intervertebral discs (PLID). Methods. Records of 296 men and 102 women aged 19 to 60 (mean, 39) years who underwent discectomy for a primary PLID, and 14 men and 4 women aged 28 to 50 (mean, 40) years who underwent revision discectomy for a recurrent ipsilateral (n=14) or contralateral (n=4) PLID at L4–5 (n=14), L5-S1 (n=3), or L3–4 (n=1) were reviewed. The pain-free interval, side and degree of herniation, operating time, length of hospital stay, and pre- and post-operative visual analogue score (VAS) for pain were recorded. Clinical outcomes were evaluated using the modified Macnab criteria and the Oswestry Disability Index. Results. Patients were followed up for one to 4 years. The mean operating time was significantly longer in revision discectomy (65 vs. 141 minutes, p<0.001, unpaired t -test). There was no significant difference between revision and primary discectomy in terms of length of hospital stay or clinical improvement rates. Age, gender, smoking, profession, level and extent of herniation, and pain-free interval did not affect clinical outcomes. In the 18 revision cases, the mean pain-free interval until recurrence was 31 (range, 1–42) months. At the one-year follow-up, results were excellent in 8, good in 6, fair in 3, and poor in one. Three of the patients had persistent pain despite taking analgesics. 14 of the patients had returned to their normal daily activities. Complications included foot drop (n=1), dural tear (n=3), and superficial wound infection (n=1). Conclusion. Discectomy achieved satisfactory results for both primary and recurrent PLIDs.